The internationalization of the RMB, capital market openness, and financial reforms in China - Joshua Aizenman (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​This paper provides an overview of Chinese financial and trade integration in recent decades, and the challenges facing China in the coming years. China had been a prime example of export-led growth, benefiting from learning by doing, and by adopting foreign know-how, supported by a complex industrial policy. While the resultant growth has been spectacular, it comes with hidden but growing costs and distortions. The Chinese export-led growth path has been challenged by its own success, and the Global Financial Crisis forced China toward rebalancing, which is a work in progress. Reflecting on the internationalization of the CNY, one expects the rapid accelerating of the commercial internationalization of the CNY. In contrast, there are no clear-cut reasons to rush with the full CNY financial internationalization: The gains from CNY financial internationalization are overrated. Publication
URN:NBN:fi:bof-201502231048
Keywords: E60; F36; F40; F60; O24; O40; 330; export led growth; CNY internationalization; mercantilism; financial integration; FDI